2020
DOI: 10.1111/cico.12515
|View full text |Cite
|
Sign up to set email alerts
|

“Not Just a Lateral Move”: Residential Decisions and the Reproduction of Urban Inequality

Abstract: Despite decades of research on residential mobility and neighborhood effects, we know comparatively less about how people sort across geography. In recent years, scholars have been calling for research that considers residential selection as a social stratification process. In this paper, we present findings from work our team has done over the last 17 years to explore how people end up living where they do, relying in large part on systematically sampled in-depth narrative interviews with families. We focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 144 publications
1
23
0
Order By: Relevance
“…It is clear from the literature on schooling inequality that race shapes schooling. Students of color, particularly Black and Latinx students, are disproportionately under-represented in well-resourced schools (Bankston & Caldas, 2000;DeLuca & Jang-Trettien, 2020;Dougherty et al, 2009;Emerson et al, 2001). Even among integrated schools, tracking practices place students of color into less rigorous classes than those taken by whites (Lewis & Diamond, 2015;Lewis-McCoy, 2014;Ochoa, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from the literature on schooling inequality that race shapes schooling. Students of color, particularly Black and Latinx students, are disproportionately under-represented in well-resourced schools (Bankston & Caldas, 2000;DeLuca & Jang-Trettien, 2020;Dougherty et al, 2009;Emerson et al, 2001). Even among integrated schools, tracking practices place students of color into less rigorous classes than those taken by whites (Lewis & Diamond, 2015;Lewis-McCoy, 2014;Ochoa, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to school choice, scholars have also traced several between-school mechanisms that work to maintain unequal access to resources through race and class-based segregation across schools (Kozol, 2005), influenced by decades of redlining and the racial wealth gap (Hao, 2007;Oliver & Shapiro, 2006). Residential segregation blocks Black and Latinx students access to (most often) white, middle-class neighborhoods with higher tax bases, thus creating racial disparities in per-student spending (Bankston & Caldas, 2000;DeLuca & Jang-Trettien, 2020;Dougherty et al, 2009;Emerson et al, 2001). 3 Social scientists have extensively examined the persistent "racial achievement gap, " the trend where Black and Latinx students continually score lower on national tests as compared to their white and Asian counterparts, as linked to disparities in resources across schools (Kao & Thompson, 2003;Merolla & Jackson, 2019).…”
Section: Racializing Schoolsmentioning
confidence: 99%
“…Continued segregation patterns, under choice theory, are partly a function of residential preferences and the fact that Blacks are often the least preferred neighbors and are therefore often segregated in pockets of poverty and disadvantage (Bobo and Zubrinsky, 1996;Charles, 2001). From this 3 Research documents that poor families often make unplanned housing decisions under strained and evolving conditions related to employment, criminal records, immigration status, and eviction (DeLuca and Jang-Trettien, 2020;DeLuca et al, 2019), all of which further constrain their housing options. Unregulated home transfers outside of the mortgage market in Black neighborhoods may also place buyers in vulnerable positions, further exacerbating racial inequalities in housing (Jang-Trettien, 2021).…”
Section: Multigenerational Neighborhood Exposurementioning
confidence: 99%
“…Moreover, these preferences are likely to change with circumstances and age [e.g. 33 , 37 , 38 ]. It has also been shown that “desirable” neighbourhoods are more easy to predict than, for instance, rural areas [ 39 ].…”
Section: Introductionmentioning
confidence: 99%